2023
DOI: 10.1101/2023.05.25.542301
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuroanatomical and functional dissociations between variably present anterior lateral prefrontal sulci

Abstract: The lateral prefrontal cortex (LPFC) is an evolutionarily expanded region in humans that is critical for numerous complex functions, many of which are largely hominoid-specific. While recent work shows that the presence or absence of specific sulci in anterior LPFC is associated with cognitive performance across age groups, it is unknown whether the presence of these structures relates to individual differences in the functional organization of LPFC. To fill this gap in knowledge, we leveraged multimodal neuro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 116 publications
(266 reference statements)
0
3
0
Order By: Relevance
“…Notably, the studies covered different age ranges-ages 22-36 vs. 6-18-and also used different cognitive measures [our previous study used WISC-IV Matrix Reasoning task (Wechsler 1949) and the Woodcock-Johnson Psychoeducational Battery Cross Out task (Brown et al 2012)]. Thus, taken together, these findings establish a robust anatomical-behavioral association that does not generalize to all forms of cognition or to all sulci, which converges with the observed functional dissociation between neighboring sulcal components (Willbrand et al 2023a).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Notably, the studies covered different age ranges-ages 22-36 vs. 6-18-and also used different cognitive measures [our previous study used WISC-IV Matrix Reasoning task (Wechsler 1949) and the Woodcock-Johnson Psychoeducational Battery Cross Out task (Brown et al 2012)]. Thus, taken together, these findings establish a robust anatomical-behavioral association that does not generalize to all forms of cognition or to all sulci, which converges with the observed functional dissociation between neighboring sulcal components (Willbrand et al 2023a).…”
Section: Discussionmentioning
confidence: 62%
“…We found that children and adults with left pimfs-v had on average 28% and 34% higher reasoning scores, respectively, than those without it. In the same sample of younger adults, we recently showed that pimfs-v and pimfs-d exhibited different patterns of large-scale resting-state functional connectivity, whereby the pimfs-v was associated with control-related networks and the pimfs-d was associated with attention-related networks (Willbrand et al 2023a). Thus, the present behavioral dissociation between these sulcal components likely stems from participation in different brain networks and cognitive functions.…”
Section: Discussionmentioning
confidence: 98%
“…To determine if the slocs-v is functionally distinct from surrounding sulci, we generated functional connectivity profiles using recently developed analyses [12,13,53]. First, we used resting-state network parcellations for each individual participant from Kong and colleagues [54],…”
Section: (F) Functional Analysesmentioning
confidence: 99%